Studies on Lyme disease incidence rates in selected groups of forestry workers in West Pomerania, 2005-2014 - Tomasz Stawicki (Nofer Institute of Occupational Medicine, 2017)
Background: The data collected by sanitary-epidemiological stations in 2005-2014 were analyzed to determine the incidence rates of borreliosis Lyme disease in the West Pomerania group of workers exposed to tick bites. Material and Methods: It was assumed that an adequate comparison of official epidemiological data with the data concerning the number of exposed people, is an indispensable condition for assessing properly the trend in Lyme disease incidence rates, concerning at the same time a real scale of occupational exposure. The study covered a selected group of forestry workers, i.e., white-collar staff employed in different units of the State Forests National Forest Holding with their seats in West Pomerania. The aim of the research was to process and analyze the data on workers employed in the forest sector and their positions, requested from district sanitary-epidemiological stations. Results: In the years concerned 282 cases of the occupational disease were recorded mainly in the groups of forest rangers, junior foresters and forest service inspectors. The values of the incidence factor exhibit high variability with the major share of cases recorded in the years 2008-2010 that accounted for 61.8% of the total occurrences concerned. The incidence in the years 2008, 2009 and 2010 amounted to 2418, 2828 and 2646 cases per 100 000 employees, respectively. Conclusions: The results show that previously published information about the incidence of Lyme disease in the agriculture, forestry and hunting sector, did not fully illustrate a real scale of occupational risk. Med Pr 2017;68(2):211-220